Systematic Analysis of Outcomes for Surgical Resection and Radiotherapy in Patients with Papillary Meningioma - Fong, Christina; Nagasawa, Daniel T.; Chung, Lawrance K.; Voth, Brittany; Cremer, Nicole; Thill, Kimberly; Ung, Nolan; Gopen, Quinton; Yang, Isaac (Journal of Neurological Surgery Part B: Skull Base, 2015)
Introduction Papillary meningiomas (PMs) are characterized by their aggressive nature and high rate of recurrence. Due to their rarity, studies examining the relationship between treatment and clinical outcomes for this disease are limited. Gross total resection (GTR) with or without radiotherapy (RT) is considered the standard treatment; however, when GTR is not feasible, subtotal resection (STR) followed by RT may be an effective alternative. In this study, we analyzed the clinical outcomes in patients who either underwent GTR alone, GTR followed by RT, STR alone, or STR followed by RT.Methods A systematic analysis was performed to identify PM patients with sufficient follow-up and outcome data, as measured by recurrence. Patient data lacking extent of resection, follow-up, or recurrence information were excluded.Results A total of 29 patients with PM were treated with resections (23 GTRs and 6 STRs).The mean age and mean follow-up of patients in this study were 32.3 years and 42.1 months, respectively. Of these patients, 58.6% experienced recurrence. Overall, 47.8% of patients who underwent GTR experienced recurrence. These patients also demonstrated improved survival compared with STR. Among patients whose tumors were only partially excised, a recurrence rate of 83% was observed.Conclusion Our results confirm that GTR results in fewer recurrences compared with STR, supporting GTR as the treatment of choice for PM. Furthermore, GTR in conjunction with RT resulted in improved survival compared with GTR alone. When GTR was not feasible, STR with RT was associated with improved survival compared with STR alone. Future studies with more outcome data are needed to elucidate the optimal treatment for this rare disease.
Keywords: papillary meningioma; papillary; meningioma; surgery; radiotherapy